Energy efficient operation for a reconfigurable and self-interleaved optical access network. (February 2018) - Niknia, Elham; Toycan, Mehmet; Walker, Stuart D.
Abstract: This paper presents a resource management of an arrayed waveguide grating for the design of access network in terms of reconfigurable bandwidth allocation and energy efficient operation. Power consumption characteristics of different channel routing mechanisms are investigated for the downstream transmission. Take-up rates of the subscribers are analyzed to estimate the required optical devices at different phases of the system. Traffic mode operation is also considered to realize the power reduction and energy efficiency for different channel routing mechanisms by the optimal use of components with respect to the active users. Proposed mechanisms are discussed in details and simulation results are presented for the energy savings on network scenario. The model which exploits free spectral range wrapping, has the most promising cost efficient device utilization, power consumption of 285 W and a minimum of 45% energy saving characteristics as compared to the conventional model.